Metodologi Tafsir Mukhtasar - Lira Erlina; M Hariyadi; Said Agil Husin Munawwar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2022)
The purpose of this study is to analyze the methodology of mukhtasar interpretation. This research uses library research methods with descriptive qualitative methods used in collecting various information from turâts and contemporary books to examine the epistemology of mukhtasar interpretations found how to determine the criteria for mukhtasar interpretation. The three ways are; first by paying attention to the quantity of an interpretation. Second; analyzed from the content of the interpretation. Third, the provisions of the scholars in assessing it. In this study, it was also found that the interpretation of mukhtasar when viewed from the source side consists of two forms; tafsir mukhtasar bi al-ma'tsûr and tafsir mukhtasar bi ar-ra'yi. The main source of mukhtasar interpretation in addition to the sources previously mentioned is the parent interpretation, namely the interpretations summarized by the mufasir. In terms of method, mukhtasar interpretation is a category of ijmâliy interpretations that interpret verses concisely and easily understood with two models of interpretation; i.e. tafsir mukhtasar ibtidâ'iy or tafsir mukhtasar bizâtihi and tafsir mukhtasar which summarizes the parent interpretation or is named after the interpretation of mukhatsar min ghairihi.